Evaluation of Compliance Abstracts of Persian-language Journals Tehran University of Medical Sciences with ISO 214 & Vancouver's Group Guideline , in 2009 - L Abdollahi; H Abdekhoda (Tehran University of Medical Sciences, 2010)
Background and Aim: Homogeneity and Oneness is the feature of abstracting. These can't be achieved, without adherence to guidelines and international standards. The purpose of this study is evaluation of compliance abstracts of Persian-language journals of Tehran University of Medical Sciences, with ISO 214 & Vancouver's group guideline, in year 2009.Materials and Methods: Survey-descriptive method was adapted. The study sample included all full-text journal Reviews in English Persian language belonging to Tehran University of Medical Sciences. These journals were significant in TUMS website to date (30/2/2009). Total 100 abstracts from the latest issue of the journal articles for instance, were randomly selected. The data collected through two control lists separately, reflecting the standards of ISO 214 and instructions group in Vancouver for abstract writing. The data were analyzed by software and statistical techniques.Results: The average overall rate of compliance with ISO standards Review is 85/37 percent (SD 24/93 percent), and group instructions Vancouver is 84/44 percent (SD 24/36). Review of the "express findings" had the most and the "sub results presented" had minimum compliance with ISO standards. The "keyword existence" and "noted the findings" had the most and the "being derived from the headings keywords subject had "minimum compliance with the instructions in Vancouver group.Discussion and Conclusion:. The abstract compliance with ISO 214 and Vancouver instruction was desirable. More comply from ISO 214 in "results presented" and Vancouver group instruction in, keywords subject in medicine seems to be required.